ORNAMENTS OF LAPO BATAKIN KUALA TANJUNG, BATUBARA REGENCY A SEMIOTICS INTERPRETATION - Elisa Betty Manullang; Windy Lizasadela (Jurnal Darma Agung, 2021)
This article aims to clarify the semiotic meaning in Lapo Batak ornaments in Kuala Tanjung, Batubara Regency. The data of this study were taken from the interpretation from Batak Toba people who live in Kuala Tanjung, Batubara Regency is located in North Sumatera Indonesia in interpreting their cultural symbols. In clarifying the data, the writer was conducted by using qualitative method. The result showed the semiotic meaning and how the cultural values were realized in Lapo Batak ornaments. The dates were analysed by using Roland Barthes’ order of signification theory; denotation, connotation, and myth to emphasize the interaction between the sign with the personal cultural experience of the viewers, and the interaction between convention in the sign with the conventions experienced and expected by viewers. The writer found that the interpretations of the personal cultural experience from the viewers were still far from the Batak Toba convention (myth) in interpreting the ornaments.